2023
DOI: 10.1371/journal.pone.0285717
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin prescribing and therapeutic drug monitoring: Challenges of real clinical practice

Mariam Hantash Abdel Jalil,
Rima Ηijazeen,
Farah Khaled Abu-Mahfouz
et al.

Abstract: Background Vancomycin prescription and monitoring guidelines have been reported to be poorly followed by various centers. Aims Identifying barriers to compliance with vancomycin dosing and therapeutic drug monitoring guidelines (TDM) and possible ways to enhance compliance based on the healthcare providers’ (HCPs) perspective. Methods A qualitative study based on semi-structured interviews with HCP (physicians, pharmacists, and nurses) was conducted at two Jordanian Teaching Hospitals. Interviews were audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We previously conducted a meta-analysis including 19 studies with 2,598 patients from developed countries such as the United States, Japan, Australia, and New Zealand, and developing countries such as China and India, and showed that the mean vancomycin trough concentration attainment rate was 34.3% under the conventional physician-led model of care (Kunming et al, 2023). Factors contributing to the unsatisfactory status of monitoring under physician-led vancomycin TDM included negative perception towards prescription guidelines, lack of knowledge regarding TDM guidelines, the hierarchy of medication management, work pressure, and ineffective communication among healthcare providers (Abdel Jalil et al, 2023). Our further analysis showed that 64.6% (281) of the patients were given vancomycin at 1g q12 h, which was a conventional dose.…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted a meta-analysis including 19 studies with 2,598 patients from developed countries such as the United States, Japan, Australia, and New Zealand, and developing countries such as China and India, and showed that the mean vancomycin trough concentration attainment rate was 34.3% under the conventional physician-led model of care (Kunming et al, 2023). Factors contributing to the unsatisfactory status of monitoring under physician-led vancomycin TDM included negative perception towards prescription guidelines, lack of knowledge regarding TDM guidelines, the hierarchy of medication management, work pressure, and ineffective communication among healthcare providers (Abdel Jalil et al, 2023). Our further analysis showed that 64.6% (281) of the patients were given vancomycin at 1g q12 h, which was a conventional dose.…”
Section: Discussionmentioning
confidence: 99%